Model McKinsey dalam Pengembangan Kapasitas Kelembagaan pada Perusahaan Daerah Air Minum Kota Makassar - Subhan Djaya; Abdul Mahsyar (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The organization's implementation in achieving its objectives is largely determined by the extent of the capacity formed to produce optimal performance. This research aims to find out how to develop capacity in Regional Companies and offers a model of capacity building. This research took place at the Makassar Water Supply Company using a descriptive-qualitative approach, the data source obtained from the research informant consisted of directors and middle management level officials, members of the supervisory board, the Chairman of the Regional House of Representatives, experts in the field of management, NGO's that actively monitor the performance of Regional Companies as primary data sources, and secondary data sources obtained from documents available at related agencies. Research data obtained through interviews, observations, secondary data support. Data analysis is conducted based on qualitative analysis through data reduction stages, data presentation, conclusion drawing, and data verification. The results showed that capacity building based on Mc Kinsey capacity building framework in Makassar Water Supply Company has been applied to the aspects of aspirations, strategies, organizations skills, human resources, organization structure, system and infrastructure, and culture. The application looks strong on the aspects of aspirations, strategies, and organization structures, which seems to require development in the aspects of organizations skills, system and infrastructure, human resources, and culture.